PENERAPAN RESTORATIVE JUSTICE TERHADAP ANAK BERHADAPAN DENGAN HUKUM DALAM TINDAK PIDANA PENCURIAN (STUDI DI KEJAKSAAN NEGERI SERDANG BEDAGAI) - Girsang, Cosman Oktaniel; Eddy, Triono (JURNAL DOKTRIN REVIEW, 2023)
Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (UUSPPA), regulates the resolution of children's cases by prioritizing the principles of restorative justice, the aim of which is to resolve in order to achieve justice. The formulation of the problem is what the criminal law policy is for ABH in the crime of theft, and how restorative justice is arranged for ABH, as well as how the Serdang Bedagai District Attorney's efforts are to implement restorative justice against ABH. Empirical juridical research methods. The results of the research are ABH's criminal law policy in criminal acts of theft, namely that children under 12 years of age are only given back to their parents, and restorative justice arrangements. Article 1 paragraph 6 UUSPPA explains restorative justice as the resolution of criminal cases involving the perpetrator. victims, families, to find a just solution with reinstatement, as well as efforts by Prosecutor Sergei to implement restorative justice against ABH, Article 7 Paragraph (2) UUSPPA formulates that Diversion must be pursued at the level of Investigation, Prosecution and examination of children's cases at the District Court, efforts This is a diversion deliberation. As a suggestion, in the criminal law policy towards ABH, the government should make regulations that prevent children from repeating their mistakes, such as child-friendly social punishments, and the opportunity to carry out diversion deliberations should not be limited to 30 days, because this time is very short and As a result, law enforcers have difficulties and diversion deliberations do not run optimally, and every law enforcement agency office that will carry out diversion deliberations should have a child-friendly room.